Upaya Meningkatkan Kemampuan Membaca Awal Huruf Hijaiyyah Pada Anak Usia 4-5 Tahun Melalui Media Flashcard di Kober Al-Mahmudin - Ramdani, N. Fitri; Ashshidiqi Poppyariyana, Alfian; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
This research aims to improve the ability to recognize the beginning of hijaiyyah letters in children aged 4-5 years through the use of flashcard media. The problem found in Kober Al-Mahmudin is the low ability of children to recognize hijaiyyah letters, which is caused by the lack of use of interesting learning media and in accordance with the characteristics of early childhood. This study uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The subjects of this study are 15 children aged 4-5 years in Kober Al-Mahmudin. Data were collected through observation, interviews, and documentation, and analyzed in a qualitative and quantitative descriptive manner. The results of the study show that the application of flashcard media can improve the ability to recognize the beginning of hijaiyyah letters in children. In the first cycle, the percentage of children's ability to recognize hijaiyyah letters reached 65%, and increased to 90% in the second cycle. In addition, children show increased interest and enthusiasm in the learning process. In conclusion, flashcard media has proven to be effective in helping early childhood recognize hijaiyyah letters more easily and fun. Therefore, it is recommended that educators in Early Childhood Education (PAUD) use interactive and interesting learning media to support optimal child development.